A context-independent situational judgment test to measure prosocial implicit trait policy. Issue 4 (7th August 2016) - Motowidlo, Stephan J.; Ghosh, Kamalika; Mendoza, Anjelica M.; Buchanan, Ashley E.; Lerma, Mikal N.
ABSTRACT: Two studies developed and validated a context-independent situational judgment test (SJT) of prosocial implicit trait policy (ITP). The first study developed a SJT based on critical incidents about the prosocial behavior of physicians, lawyers, community service volunteers, and human factors engineers. In a sample of 396 undergraduates, scores obtained from this SJT were internally consistent and correlated significantly with other trait constructs related to prosocial ITP. In the second study with 134 undergraduates, the SJT was significantly correlated with relevant trait constructs and prosocial performance in role-plays simulating scenarios in which others needed help. These results show that a generic SJT developed from items that describe situations and actions specific to several occupations can predict behavior in situations unlike any that appear in its items.